Comparison of Fuzzy Logic and Genetic Algorithm Based Admission Control Strategies for UMTS System - P. Kejík; S. Hanus (Radioengineering, 2010)
CDMA systems have so-called soft capacity, so the total number of possible sessions has not an exact value. The capacity of CDMA system depends on the interference level in the system. There are therefore RRM (Radio Resources Management) functions, which are responsible for supplying optimum coverage, ensuring efficient use of physical resources and providing the maximum planned capacity. This paper presents and compares several algorithms that are used for admission control purposes in UMTS system. Several versions of fuzzy logic based algorithms, load factor based algorithm and genetic based algorithm are mutually compared via simulations.